Differential effects of variance in prey arrival on foraging success and growth rate of two pit‐building antlion species. (3rd July 2017) - Barkae, E. D.; Scharf, I.; Ovadia, O.
Abstract: Animals in nature generally face fluctuating rather than constant environmental conditions. When given a choice, animals usually seek to minimize the variance of gain. However, it is clear that the avoidance of variance in energetic gain depends on several factors, including hunger level. While holding the mean prey encountered constant, we studied the effect of variance in prey arrival on the growth rates of two pit‐building antlion species, Myrmeleon hyalinus and Cueta lineosa . Both species construct pit‐traps in loose soils and ambush small prey in the same desert habitats, while differing in their preferred microhabitat: shaded vs. exposed to direct sunlight. We expected the light‐preferring species to better tolerate variance in feeding than the shade‐preferring species, owing to the former's higher stress tolerance and natural occurrence in microhabitats that are more likely poor with prey. While increasing variance in prey arrival reduced the growth rates of both species, this decrease was more pronounced in the species inhabiting the shaded and most likely prey‐richer microhabitat. The greater variance tolerance of the light‐preferring species stems from its ability to capture several prey items when almost simultaneously encountered. It could also be that this species has lower basal metabolic rate, which improves its starvation tolerance. These two antlion species differed in their prey capture success, starvation and thermal tolerance, and we thus suggest that their tolerance to variance in feeding opportunities and functional response offer an additional axis that enables them to coexist in the same desert habitats. Abstract : We studied the effect of variance in prey arrival on the growth rates of two pit‐building antlion species, while holding the mean prey encountered constant. Both species construct pit‐traps in loose soils and ambush small prey in the same desert habitats, while differing in their preferred microhabitat: shaded vs. exposed to direct sunlight. While increasing variance in prey arrival reduced the growth rates of both species, this decrease was more pronounced in the species inhabiting the shaded and most likely prey‐richer microhabitat. The greater variance tolerance of the light‐preferring species stems from its ability to capture several prey items when almost simultaneously encountered. This may be related to the light‐preferring species' occurrence in microhabitats that are probably poor with prey. The difference between the two antlion species in their tolerance to variance in prey arrival may be an additional axis that enables them to coexist.